2015
DOI: 10.4028/www.scientific.net/kem.659.116
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Zirconia Toughened Alumina Fabricated by Powder Injection Moulding

Abstract: Zirconia toughened alumina (ZTA) ceramic has been fabricated by the powder injection moulding process. The ZTA ceramic, composed of 80 wt% alumina and 20 wt% zirconia, was mixed with a water-soluble, multi-component binder system. The binder ingredients were polyethylene glycol (PEG), polyvinyl butyral (PVB) and stearic acid (SA). Powder injection moulding was performed with powder loadings in the range of 48-52 vol%, using a laboratory-scale injection moulding machine. Water leaching was used for partial bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…(ZTA) Composites consist of an alumina-rich composition where the matrix microstructure is modified by zirconia as a second phase. The even dispersion of zirconia in the alumina matrix produces a ceramic body with superior strength and toughness, improved chemical stability [12], an appropriate thermal conductivity of about 20 W/mK, and a composite body serving at an elevated temperature of about 1650-1700°C [13,14]. At the same time, alumina does not lose its high hardness and stability by preventing crack propagation and abnormal grain growth [12].…”
Section: Zirconia-toughened-alumina (Zta)mentioning
confidence: 99%
“…(ZTA) Composites consist of an alumina-rich composition where the matrix microstructure is modified by zirconia as a second phase. The even dispersion of zirconia in the alumina matrix produces a ceramic body with superior strength and toughness, improved chemical stability [12], an appropriate thermal conductivity of about 20 W/mK, and a composite body serving at an elevated temperature of about 1650-1700°C [13,14]. At the same time, alumina does not lose its high hardness and stability by preventing crack propagation and abnormal grain growth [12].…”
Section: Zirconia-toughened-alumina (Zta)mentioning
confidence: 99%
“…This might have occurred due to increase in the hardness in the polymer nanocomposite material. Chuankrerkkul et al [27] have reported that, when ZTA nanopowder is reinforced into a polymer matrix, it enhances the hardness significantly in the parent material. In our case, the increase in hardness has further led to increase in the brittle nature and stiffness of the polymer nanocomposite.…”
Section: Ac Conductivitymentioning
confidence: 99%
“…Gradient ceramics, in particular, Al 2 O 3 -ZrO 2 -based systems, are replacing several structural metals and alloys. Composite ceramics based on aluminum oxide and zirconium dioxide are used to make cutting tools, biomedical implants, molds, parts of prostheses, bulletproof vests, oxygen sensors, and more [1][2][3][4][5][6]. Composite ceramics are characterized by some unique physical and chemical properties not found in other classes of materials, such as hardness, compressive strength, bending, high corrosion resistance, resistance to aggressive media and thermal shock, high-temperature serviceability, and thermal expansion coefficients close to those of metals and alloys [7].…”
Section: Introductionmentioning
confidence: 99%